Giardiasis: importance in the veterinary medical practice - Ferreira, Ana Paula; Destro, Flávia Caroline (Pubvet, 2020)
Giardiasis is a routine pathology in the veterinary medical practice, caused by the protozoan Giardia spp, which acts as a source of infection of several species, especially dogs and humans, and is considered a zoonosis of great importance for public health. Young, immunosuppressed dogs attending public places have a higher incidence for the disease. Contamination is due to the ingestion of mature Giardia spp cysts found in the feces of infected animals, water and contaminated food. The need for proper hygiene of the environment, in which dogs reside, in order to avoid contamination with other animals and between humans, is of great importance in the control of giardiasis
Keywords: Giardia canis; dogs; cysts